Analisis Keruangan Terhadap Perubahan dan Persebaran Permukiman Kumuh di Kecamatan Banjarsari Kota Surakarta Tahun 2001-2005 - Dahroni, D (Universitas Muhammadiyah Surakarta, 2008)
Since the year 1998 up to the mid of 2005, in the district ofBanjarsari, there happened an increasing amount of slum areas which might endanger the environmental balance. This research aims at (1) identifying the shift of distribution pattern from the settlement diffusion in the district of Banjarsari Surakarta in the year 2001-2005. (2) Identifying the alteration form of the unoccupied land into slum areas in the district of Banjarsari Surakarta. (3) Identifying the characteristics of slum area dwellers in the district of Banjarsari Surakarta. This research uses the survey method, secondary data analysis and map analysis. The data ar alysis used is tlie closest neighbor analysis, table of frequency, crossed tables and descrip ave analysis. The result shows that (1) the distribution pattern of the slum areas appeared in the district ofBanjarsari in the year 2001 is the random distribution pattern while the one in 2005 is the dissemination pattern. Such pattern indicates the grc wing amount and interraction with the means of transportation and economic condition in those slum areas. (3) The lands which are altered into slum areas in the district of Banjarsari during 2001-2005 take place in the unoccupied areas owned by the state.(3) The distribution of age among the slum area inhabitants is around 41-61 years of age (49%) while tb biggest amount is the new arrivals (57%). The region of Sub province Sragen has the bigges percentage in the distribution of the city inhabitants origin in the district of Banjarsari. Regionally, the inhabitants who come from the hinterland of Surakarta or ex Surakarta residency took the amount lof 73.68%. The highest percentage of educational level of the slum area inhabitants in the district of Banjarsari is the uneducated residents or those from low education level (55%). Most of the respondents occupations of the slum area dwellers in Banjarsari are in the informal sectors (82%) The number of family member in the district of Banjarsari is around l-